Chlorophyll a measurements from discrete water samples during RV MARIA S. MERIAN cruise MSM65 (2017-06-25 – 2017-07-19, GREENHAB II) - Daniela Voß; Daniela Pieck; Veloisa J Mascarenhas; Oliver Zielinski (PANGAEA, 2025)
This dataset was collected during the cruise MSM65 (GREENHAB II, 2017-06-25 – 2017-07-19) with RV MARIA S MERIAN from St. John extquotesingles, Canada to Nuuk, Greenland. It contains chlorophyll a measurements [μg/L] from water samples collected from discrete sampling via CTD. In total, 46 stations have been sampled from various depth. To obtain chl-a concentrations water samples were filtered onboard through 0.7 μm pore size, glass fiber filters (Whatmann GF/F) under low vacuum. Filters were frozen immediately at -80 °C until extraction in laboratory via 90% acetone. Concentrations were calculated from fluorescence measured with a pre-calibrated Turner Design TD700 laboratory fluorometer (EPA445.0, Arar & Collins, 1997).